2018
DOI: 10.1371/journal.pone.0192803
|View full text |Cite
|
Sign up to set email alerts
|

Macro-morphological characterization and kinetics of Mortierella alpina colonies during batch cultivation

Abstract: An effective method for research of macro-morphological characterization and its kinetics was developed by studying the macro-morphological characteristics of Mortierella alpina, an oleaginous zygomycete widely used to produce lipids rich in PUFA, in function of culture medium composition and to link morphological features of fungus with the level of lipid production. A number of distinct morphological forms including hollow pellets, fluffy pellets and freely dispersed mycelia were obtained by changing the fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…With the exception of maximum specific growth rate, the altered kinetic values (i.e., m S , k dD , and k dL ) found in the engineered A. oryzae strain when grown in different culture media (NaNO 3 -defined and CSH/ML media) indicated that the lipid metabolites are dynamic molecules in leveraging several cellular metabolisms during the cell growth, probably for maintaining cell homeostasis. It can be documented that the generated logistic equation could explained well the fungal growth, which was similar to the previous studies of other oleaginous fungi and yeast (Amirsadeghi et al, 2015;Fang et al, 2018;Xu et al, 2018). In addition, the Luedeking-Piret equation, which was modified by including the term of lipid degradation, could describe the phenomena of lipid production and degradation as well as DGLA production.…”
Section: Strains Parameters Referencessupporting
confidence: 80%
“…With the exception of maximum specific growth rate, the altered kinetic values (i.e., m S , k dD , and k dL ) found in the engineered A. oryzae strain when grown in different culture media (NaNO 3 -defined and CSH/ML media) indicated that the lipid metabolites are dynamic molecules in leveraging several cellular metabolisms during the cell growth, probably for maintaining cell homeostasis. It can be documented that the generated logistic equation could explained well the fungal growth, which was similar to the previous studies of other oleaginous fungi and yeast (Amirsadeghi et al, 2015;Fang et al, 2018;Xu et al, 2018). In addition, the Luedeking-Piret equation, which was modified by including the term of lipid degradation, could describe the phenomena of lipid production and degradation as well as DGLA production.…”
Section: Strains Parameters Referencessupporting
confidence: 80%
“…In general, the morphology of filamentous fungi could be divided into three types: dispersed mycelia, clumps, and dense pellets [ 12 ]. Moreover, the final products can exhibit significant differences in the optimal morphology [ 13 , 14 ]. For example, pellets are considered to be the optimal form in the production of glucoamylase by A. niger .…”
Section: Introductionmentioning
confidence: 99%